"Corner Shot": An Incidentally Detected Thoracic Lesion at Abdominal Imaging. Issue 4 (July 2015) - Swanson, Karen L.; Panse, Prasad M.; Jensen, Eric A.; Cummings, Kristopher W.; Gotway, Michael B.
Abstract : Bronchial carcinoid tumors are uncommon thoracic neuroendocrine neoplasms that, although malignant, usually exhibit indolent biological behavior. Bronchial carcinoid tumors are often subdivided into "typical" and "atypical" varieties, the latter more frequently associated with somewhat more aggressive behavior, advanced local disease, and lymphadenopathy. Bronchial carcinoid tumors present on chest radiography as central or hilar masses, often associated with postobstructive effects. Thoracic computed tomography often shows a central lesion, occasionally with calcification, and a clear relationship to an airway, often manifesting as an endobronchial lesion, is common. Bronchial carcinoid tumors may occasionally be detected in asymptomatic patients undergoing imaging for incidental reasons. Peripheral carcinoid tumors occur in 15% of the patients, and calcify less frequently than their central counterparts. 2-[ 18 F]-Fluoro-2-deoxy-D-glucose positron emission tomography scans often do not show elevated tracer uptake within bronchial carcinoid tumors. Bronchial carcinoid tumors usually do not produce paraneoplastic syndromes in the absence of metastatic disease; when a paraneoplastic syndrome is present, Cushing syndrome is most commonly encountered. Bronchoscopy and somatostatin scintigraphy are very useful for establishing the diagnosis of carcinoid tumor. The treatment of carcinoid tumors is usually surgical, with typical carcinoid tumors showing excellent 5-year survival rates, with still good, but relatively diminished, 5-year survival rates for atypical carcinoid tumors.